The Influence of Leadership Style and Independence on Auditor Performance with Professionalism as a Moderation Variable - Siti Fauzi Nurhayati; Mia Sipa Sopiatur Rohmah; Khoirun Nuranisa Safitri (Yayasan Az Zukhruf Cendikia, 2026)
Purpose – This study aims to obtain empirical evidence about the effect of leadership style and independence on auditor performance with professionalism as a moderating variable. Design/methodology/approach – This study uses a quantitative method of primary data research. This research was conducted using a questionnaire distributed to auditors of public accounting firms (PAF) and accounting students who took audit courses, namely 40 questionnaires distributed via email and social media. Each questionnaire distributed contained 42 statements to be answered by respondents. From the distribution of questionnaires conducted, 30 respondents provided answers. To get the results of this study, researchers used PLS SEM version 3.0. Findings – The results of this study found that leadership style has an affect and is not significant on auditor’s performance, independence has a significant effect on auditor’s performance, professionalism has a significant does not moderate the relationship between leadership style and auditor’s performance, professionalism can moderate the between independence and auditor’s performance. Research limitations/implications – This study has several limitations that should be considered when interpreting the results. First, the sample size is limited to the 10 largest Islamic banks in the world, which may not fully represent the diversity of Islamic banks globally. The implications of these findings suggest that organizations need to focus on developing a supportive leadership style and creating an environment that facilitates auditor independence. Future research is advised not to use the variable professionalism as a mediator and explore other factors that might affect this relationship, in order to gain a more comprehensive understanding of the dynamics of auditor performance.